Mechanism and control of deformation in mining roadways with hard roofs in extra-thick coal seams - Gu, Wen-Zhe; Zhang, Bei-Yan; Liu, Cheng-Yong; Yuan, Chao-Feng; Yang, Yan-Bin; Liu, Wen-Tao; Zhang, Xin-Fu; Qiu, Heng-Jian (Frontiers in Materials, 2025)
IntroductionThe mining roadways for the exceptionally thick coal seams 3-5 at Tashan Colliery in the Datong Mining District faced the challenge of significant and uncontrollable surrounding rock deformation under hard roof strata conditions, posing a serious threat to safe and efficient operations.MethodsA systematic methodology combining field investigation, theoretical analysis, numerical modeling, and engineering practice was employed. Rock mechanics tests and borehole imaging were first conducted to determine the physico-mechanical parameters and joint characteristics of the surrounding rock in the 5,230 auxiliary haulage roadway. FLAC3D simulation was then used to analyze the deformation behavior of the roadway under different mining phases. Subsequently, a mechanical model of the sectional coal pillar was established based on load estimation to analyze the pressure relief mechanism via hard roof caving. Key caving parameters were optimized using UDEC numerical simulation.ResultsThe numerical simulation optimized the critical roof caving parameters: a caving height of 36 m and a caving angle of 11°. Furthermore, the optimal support parameters were determined as an anchor cable length of 5.5 m, a spacing of two cables per row, and a grouting pressure of 3 MPa. Field industrial trials and monitoring data demonstrated that the implemented technical strategy effectively controlled the deformation of the roadway rock mass.DiscussionThe integrated technical solution of “roof cutting and pressure relief combined with hollow grouting anchor cables” successfully ensured the long-term stability of the roadway. This study provides a crucial theoretical foundation and technical support for safe and efficient coal mining under similar geological conditions of hard roof and exceptionally thick coal seams.